1999
DOI: 10.1021/es9810641
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation of Terpenes:  Camphene, Δ3-Carene, Limonene, and α-Terpinene

Abstract: Emissions from wood dryers have been of some concern for a number of years, and recent policy changes by the Environmental Protection Agency have placed emphasis upon the gaseous emissions that lead to the formation of particulate matter as small as 2.5 μm diameter. In this qualitative study, camphene, Δ3-carene, limonene, and α-terpinene were thermally degraded in the presence of air to determine the number and kind of oxidative degradation products that might be expected under drying conditions used in proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 17 publications
5
63
1
Order By: Relevance
“…With regard to the main aromacontributing components, such as b-pinene, myrcene, and camphor, the MAHD matrix contained higher amounts than the other matrices and, moreover, the lowest amount of p-cymene. The latter is a thermal degradation product derived from a-terpinene, as a consequence of rearrangement accompanied by dehydrogenation [28].…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the main aromacontributing components, such as b-pinene, myrcene, and camphor, the MAHD matrix contained higher amounts than the other matrices and, moreover, the lowest amount of p-cymene. The latter is a thermal degradation product derived from a-terpinene, as a consequence of rearrangement accompanied by dehydrogenation [28].…”
Section: Resultsmentioning
confidence: 99%
“…This mechanism is not known, but pine needles are thicker than most grasses and have relatively high concentrations of various terpenes (White, 1994;Zhao et al, 2011), which during increases in sub-flaming temperatures are readily volatized, degrade through exothermic oxidation reactions, and rapidly condense into PM (McGraw et al, 1999). The effect of pine needle content on EF PM2.5 may be considerable in southeastern U.S. pine communities where percentage of fine fuel composed of pine needles varies from nearly zero to nearly 100 in correspondence with pine timber volume and its competitive effects on herbaceous fuels (Wolters, 1981;Harrington and Edwards, 1999;Pecot et al, 2007;Robertson and Ostertag, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Swisher and Swisher (1977) reported that distilled oil, which is recovered from peels by steam distillation, possesses an odour and flavour that is generally inferior to that of the cold-pressed oil. McGraw, Hemingway, Ingram, Canady, and McGraw (1999) observed that terpene compounds (camphene, d-carene, limonene, and a-terpinene) degrade at high temperatures and turn into other terpene hydrocarbons and oxide terpenes. In the study of PerezCacho, Galan-Soldevilla, Mahattanatawee, Elston, and Rouseff (2008) off-flavours were caused by compounds such as p-cymenes, carvones.…”
Section: Comparison Of Peel Oils Prepared From Cold-pressed and Steammentioning
confidence: 99%